Predicting feeding tube and tracheotomy dependence in laryngeal cancer patients. (4th March 2017) - Lavo, John Patrick; Ludlow, David; Morgan, Matt; Caldito, Gloria; Nathan, Cherie-Ann
Abstract: Conclusions: The two scales reliably measure laryngeal edema and dysfunction in laryngeal cancer patients. The eight categories from these scales, and abnormal pharyngeal squeeze, can be used to form a new rating scale intended to help clinicians identify and circumvent swallowing complications after chemo-irradiation. Objectives: The objectives were to compare two laryngeal edema rating scales in laryngeal cancer patients and determine if post-radiation +/− chemotherapy edema predicts dependence on a feeding tube and/or tracheostomy. Methods: A retrospective chart review between 2005–2008 revealed 28 laryngeal cancer patients status post-radiation +/− chemotherapy, with video laryngoscopies performed within 6 months after treatment. Four raters evaluated videos based on the Laryngopharyngeal Edema Scale (LES) and the Reflux Finding Score (RFS). Tracheostomy and feeding tube outcomes were then correlated with the two scales. Results: Feeding tube and tracheostomy dependence were associated with pre-treatment vocal cord paralysis, advanced T stage, and chemoradiation. Eight categories from the LES and RFS scales were significantly associated with the need for a feeding tube.